The Existence of Arabic Learning in Universities amid the COVID-19 Outbreak: Opportunities and Challenges - Ilmiani, Aulia Mustika; Ahmadi, Ahmadi (LP2M IAIN Sultan Amai Gorontalo, 2021)
The Arabic language has peculiarity and differentiating characteristics that distinguish it from other foreign languages. This study investigates the existence of Arabic language learning during the pandemic period by conducting a thorough review of the Arabic language learning process from both an internal and an external standpoint. The method of writing this article is based on a study of literature comparison. The author conducts an online search for primary literature using valid criteria, and a reputable source—data analysis is performed using the content analysis paradigm. This study demonstrated the positive impact on the internal environment: 1) Lecturers and students gained greater proficiency in using applications that can be integrated into the learning process. 2) The assignment method changes from academic to project-based assignments, 3) Students become more proficient in using social media as tools for learning. 4) Arabic learning occurs from any location and at any time of day. The internal negative consequences are as follows: 1) memorizing qawaid or tashrif, in which case it is not easy to assess students' abilities through online instruction without face-to-face interaction; 2) Explanation of the material when face to face is considered more straightforward; 3) Unstable networks cause the inability to concentrate and focus. The external consequences are as follows: 1) a large number of linguistic webinars about Arabic, 2) The number of research references, research articles, and scientific journals are growing; 3) It is becoming easier to hold memorandums of understanding between collages from different regions.